Impact of glyphosate and glyphosate‐based herbicides on the freshwater environment. Issue 5 (25th February 2014) - Annett, Robert; Habibi, Hamid R.; Hontela, Alice
ABSTRACT Glyphosate [N‐(phosphonomethyl) glycine] is a broad spectrum, post emergent herbicide and is among the most widely used agricultural chemicals globally. Initially developed to control the growth of weed species in agriculture, this herbicide also plays an important role in both modern silviculture and domestic weed control. The creation of glyphosate tolerant crop species has significantly increased the demand and use of this herbicide and has also increased the risk of exposure to non‐target species. Commercially available glyphosate‐based herbicides are comprised of multiple, often proprietary, constituents, each with a unique level of toxicity. Surfactants used to increase herbicide efficacy have been identified in some studies as the chemicals responsible for toxicity of glyphosate‐based herbicides to non‐target species, yet they are often difficult to chemically identify. Most glyphosate‐based herbicides are not approved for use in the aquatic environment; however, measurable quantities of the active ingredient and surfactants are detected in surface waters, giving them the potential to alter the physiology of aquatic organisms. Acute toxicity is highly species dependant across all taxa, with toxicity depending on the timing, magnitude, and route of exposure. The toxicity of glyphosate to amphibians has been a major focus of recent research, which has suggested increased sensitivity compared with other vertebrates due to their life history traits and reliance on both the aquatic and terrestrial environments. This review is designed to update previous reviews of glyphosate‐based herbicide toxicity, with a focus on recent studies of the aquatic toxicity of this class of chemicals. Copyright © 2014 John Wiley & Sons, Ltd.